Revitalization Of Cultural Heritage Area with Sustainable Tourism Approach, Case Study: Tindoi Fort, Kabupaten Wakatobi - Jauhar; Purwanita Setijanti; Arina Hayati (Journal of Architecture & Environment, 2021)
Tindoi Fort continues to be threatened because of not yet get the full support of the community to preserve. Tindoi Fort should be a valuable asset for the government if it is managed seriously. The purpose of this study is to revitalize cultural heritage sites by providing new vitality through a sustainable tourism approach. The study uses a combination of interpretative historical strategies, to find out the original form of the fort through observation and in-depth interviews. Then a qualitative strategy with a descriptive approach is used to determine the social character and community culture locally so that can support tourism activities. The results of this study are the formulation of the criteria and concept of revitalization including the physical restoration of the fort, the arrangement of tourism based on environmental conservation, the arrangement of the creative economy center, the arrangement of socio-cultural activity areas that support local wisdom attractions.